(untitled) (The Agriculturists, 2010)
An experiment was conducted in a farmers field at Loknathpur in Chuadanga district under AEZ-11 (high ganges river floodplain) during 2005-06 and 2006-07 to determine the optimum irrigation level for the best performance of four sugarcane varieties (Isd 16, Isd 32, Isd 34, Isd 35). The experiment was laid out in two factors split-plot design with four irrigation levels in main plots and four varieties in sub-plots. Extra irrigations at 21, 28 and 35 days interval in addition to two live irrigations increased sugarcane yield from 15 to 48%. All the varieties showed higher establishment, tiller, millable cane and cane yield when irrigations were applied at 28 days interval over irrigation at 21 or 35 days interval. Variety Isd 32, Isd 34 and Isd 35 produced significantly higher yield. However, the overall performances of all of the selected varieties were satisfactory. These varieties can be cultivated for potential yield in sandy loam soil under AEZ-11 providing 5 irrigations at 28 days interval in addition to two live irrigations at 0 and 14 days after transplantation when soil bed budchip settlings are used as planting materials.